Double column fixation for type C fractures of the distal humerus by precontoured bi-condylar plating in a 90-90 pattern - Khan, Mohammad Rafiqul Islam; Laila, Atif; Rashid, Md. Harun Are; Mahmud, Muhammad Sayeed; Alam, Mohammad Shamsul (International Journal of Research in Medical Sciences, 2025)
Introduction: Distal humerus fractures, particularly Type C fractures, present significant challenges in orthopaedic trauma management due to their complexity and the intricacies involved in surgical repair. This study aimed to assess double-column fixation for type C fractures of the distal humerus by pre-contoured bi-condylar plating in a 90-90 pattern. Methods: This retrospective study was conducted in the Department of Orthopedics, Upazilla Health Complex, Munshigonj, Bangladesh, from January 2014 to January 2018. A total of 38 patients were evaluated based on set criteria. Functional outcomes were assessed using the Mayo Elbow Performance Score (MEPS) at six months. Data were analyzed using SPSS version 20.0, with descriptive statistics applied to demographics, surgical methods, and outcomes. Result: This study of 38 patients with Type C distal humerus fractures found most were aged ≤47 (71.1%) and male (55.7%). C2 fractures were most common (65.8%). Time to surgery and hospital stay increased with fracture complexity. MEPS results showed 26.7% had excellent and 57.8% good outcomes. Complications included elbow stiffness (21.1%), arthritis (13.2%), heterotopic bone (10.5%), fixation failure (7.9%), and infection (5.3%). Conclusion: Most patients had good to excellent outcomes based on MEPS. Though some experienced complications like stiffness and heterotopic ossification, overall results support the technique’s effectiveness in restoring elbow function.